CARD9 Signaling in Intestinal Immune Homeostasis and Oncogenesis - Hartjes, Lara; Ruland, Jürgen (Frontiers in Immunology, 2019)
Intestinal homeostasis requires a balanced interaction between the host innate immune system and the gut microbiota. A dysregulation of this interdependency can result in inflammatory bowel diseases (IBDs), and this dysregulation is a key pathogenic factor during the development of colorectal cancer. CARD9 is a central signalling molecule in the innate immune system, which is essential for host defence against infection. Moreover, polymorphisms in CARD9 are key risk factors for IBD development, indicating that CARD9 signalling is critical for intestinal immune homeostasis. This review summarizes recent insights into the regulation of CARD9 signalling, its pathophysiological role during IBD development via effects on the microbiota and epithelial regeneration and the pro- and antitumour immune functions of CARD9 during intestinal carcinogenesis.